International Scientific Conference "New Challenges of Economic and Business Development – 2017. Digital Economy" : Abstracts O 2017
DOI: 10.22364/ncebd.ab.2017.01
|View full text |Cite
|
Sign up to set email alerts
|

Loan Policies and Economic Development in a Globalized Environment

Abstract: Significant amount of the European Union (EU) budget has been allocated to different training programmes. In-order to plan future investments, current interventions financed by EU into national educational policies should be assessed. This research aims to perform a mid-term evaluation of the three-year (2015-2018) Erasmus+ project related to high school students' Information and Communication Technology (ICT) skill development in the selected schools of' Latvia, Sweden, the United Kingdom, Italy and Spain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Arabacı and Akıllı (2021) and Kunnari, Jiang and Myllykoski-Laine (2021) also found that the projects contributed positively to the development of teachers' Web 2.0 tools and ICT skills. In the international study of Androniceanu and Dragulanescu (2017), a three-year Erasmus+ project carried out in projectrun schools in Latvia, Sweden, the United Kingdom, Italy and Spain showed positive results in the development of ICT skills of high school teachers.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Arabacı and Akıllı (2021) and Kunnari, Jiang and Myllykoski-Laine (2021) also found that the projects contributed positively to the development of teachers' Web 2.0 tools and ICT skills. In the international study of Androniceanu and Dragulanescu (2017), a three-year Erasmus+ project carried out in projectrun schools in Latvia, Sweden, the United Kingdom, Italy and Spain showed positive results in the development of ICT skills of high school teachers.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%